Dual Regulation of Ionic Effect on Zostera marina L. Seed Germination and Leaf Differentiation in Low-Salinity Conditions - Peilong Li; Yaping Gao; Zengjie Jiang; Linjie Wang; Xiaoli Sun; Jiaqi Wang; Jing Wang; Haidong Sui; Junwei Wang; Yitao Zhang (Plants)
Low-salinity conditions are generally used in land-based cultivation to promote the germination and growth of Zostera marina L. and to improve the restoration effect of seagrass beds. Different salinity conditions lead to morphological and physiological differences. To investigate the impacts of salinity and osmotic pressure on the germination and early development of Zostera marina seeds, this study utilized seawater with different salinity conditions and PEG-6000 solutions to simulate various non-ionic osmotic pressures and examine the germination, cotyledon growth, and leaf differentiation over 28 days, as well as determine the biochemical traits on days 1, 3, 5, and 7. The results show that the cumulative germination rate in LS-0 was 91.6%, but it was not significantly affected by the PEG solutions. The different salinities (5, 10, and 15) had no significant effect on the germination rate, which ranged from 76.4% to 78.8%: low salinity and low osmotic pressure stimulated the germination by accelerating the water uptake through increased osmotic pressure differences. The leaf differentiation was regulated by the osmotic pressure and salinity. In LS-10, the most used condition, the leaf differentiation rate was 35.2%, while PEG-10 displayed 6.4%. The total soluble sugar and soluble protein in the seeds decreased. Antioxidant enzyme activities were activated under low-salinity conditions, which supported germination within a tolerable oxidative stress range.